The Saving-Investment Correlation and Capital Mobility in Asia - Kumari, Sarinder (2004)
This study assesses financial integration and international capital mobility in the Asian region by adopting the Feldstein-Horioka criterion based on the relationship between saving and investment. The analysis is carried out in two stages. The initial part of the analysis follows the standard procedure by analysing the saving retention coefficient. Using the standard time-averaged cross-sectional regression model originally employed by Feldstein and Horioka as a benchmark, a number of alternative estimation regression models are employed in this study. Of particular reference is the panel regression model proposed by Kao and Chiang (1 999) emphasized in this study. Panel unit root and panel cointegration tests that have been shown to have higher testing power are used to analyse the data. The second part of the study introduces an innovation by tracking the changes in the parameters over time to obtain evidence on whether capital mobility and financial market integration have increased over time. The empirical analysis covers 20 Asian countries at different stages of financial and economic development over the period from 1980 to 1999. The sample countries are also divided into four sub-regional samples so as to enable a comparative view of regional differences in capital mobility. The findings indicate that the close association between saving and investment is a robust empirical regularity and is consistent with other studies reported in the literature. The results of the different estimation methods including the panel regression models, confirm that the saving retention coefficient is statistically and significantly different from zero. This shows that the Asian region as a whole rejects the notion of perfect capital mobility over the sample period. Generally capital mobility is low in the Asian countries although there has been a gradual increase in capital mobility over time as shown by the changes in the saving retention coefficients. However there are regional differences with the ASEAN 5 region including Japan and Korea showing relatively higher capital mobility than the other regions.